A Study on Student Behaviour Towards Digital Payments - Banerjee, Sudip (Journal of Advanced Research in Humanities and Social Sciences, 2024)
This Research delves into the behaviour of college student regarding digital payment. Digital payment system has become prevalent, offering convenience and efficiency in financial transaction. This study aims to investigate and understand how college student uses these digital payment methods and how their perceptions of these methods influence their decision to adopt them. These systems include various type of Digital payment method like Net banking, mobile banking, apps like PhonePe and Gpay and card payment.